THE INFLUENCE OF PROMOTION AND DISCOUNT ON PURCHASING DECISIONS THROUGH CONSUMER LOYALTY ON PRODUCTS AT INFORMA SOUTH KALIMANTAN - Ernawati Ernawati; Achmad Efendy; Elya Rahmi; Imam Maliki; Syamyati Syamyati; Nasrul Nasrul (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of promotions and discounts on purchase decisions for Informa products in South Kalimantan through consumer loyalty. A quantitative approach was used with data collection via questionnaires distributed to Informa product consumers. The data were analyzed using SmartPLS 3.0 to test the direct and indirect effects between promotions, discounts, consumer loyalty, and purchase decisions. The results show that promotions do not have a significant effect on consumer loyalty, which is likely due to a lack of appeal or innovation in the promotional strategies offered. In contrast, discounts were found to have a positive and significant effect on consumer loyalty, which in turn drives repeat purchase decisions. Consumer loyalty plays an important role in purchasing decisions, with loyal consumers being more likely to continue purchasing Informa products, even when alternatives from other brands are available. Overall, the findings indicate that while promotions play a role in marketing strategies, discounts are more effective in enhancing consumer loyalty and influencing purchase decisions for Informa products. Therefore, companies are advised to optimize relevant and sustainable discount strategies to enhance loyalty and maintain competitiveness in the market.